Molecular Characterization of FT and FD Homologs from Eriobotrya deflexa Nakai forma koshunensis - Zhang, Ling; Yu, Hao; Lin, Shunquan; Gao, Yongshun (Frontiers in Plant Science, 2016)
In angiosperms, regulation of flowering is a vital process for successful reproduction. To date, the molecular mechanism of flowering is well studied in the model plant, Arabidopsis, in which key genes such as FLOWERING LOCUST (FT)or FD have been identified to regulate flowering. However, the flowering mechanisms are still largely unknown in fruit trees like loquat. To this end, we first cloned one FT- and two FD-like genes from the loquat (E. deflexa Nakai f. koshunensis) and referred to as EdFT, EdFD1 and EdFD2, respectively. Phylogenetic analysis has shown that EdFT, EdFD1 and EdFD2 are conserved during the evolution process. EdFT is mainly expressed in reproductive tissues (e.g. flower buds, flowers and fruits), while EdFD1 and EdFD2 are mainly expressed in apical buds including leaf buds and flower buds. EdFT is localized in the whole cell, while EdFD1 or EdFD2 is localized in the nucleus. Ectopic expression of EdFT, EdFD1 and EdFD2 in Arabidopsis results in early flowering. In addition, we have also revealed that the EdFT interacts with both EdFD1 and EdFD2. Overall, these data suggest that the EdFT, EdFD1 and EdFD2 are the functional homologs of FT and FD, respectively, which might act together to regulate loquat flowering through a similar mechanism found in Arabidopsis.